Dynamics of droplets and bubbles and their applications: current challenges and future opportunities - Rajneesh Bhardwaj; Myeongsub Mike Kim; Marie Pierre Krafft (Scientific Reports)
Abstract Understanding droplet and bubble dynamics in various configurations is essential for many technical applications. This collection showcases the latest research in this field, covering both fundamental and applied perspectives. Studies have employed advanced experimental and numerical methods. Topics include droplet wetting and spreading on functional surfaces, coalescence dynamics of droplets, drag reduction in microchannels, and ultrasound backscatter of bubbles.